Prawno-administracyjne aspekty bezpieczeństwa żywności i żywienia w Polsce - Maciej Jabłoński (Studia Ecologiae et Bioethicae)
Food safety and nutrition include the accumulation of concepts aimed at enforcing standards of hygiene and healthcare. In accordance with Polish and EU law, these very important issues lead to the functioning of the food market. From the ground up, compliance with environmental standards is assured at every stage.